Pure aluminium shear panels as dissipative devices in moment-resisting steel frames. - De Matteis, G. (Earthquake engineering & structural dynamics.)
The use of energy dissipation systems for the seismic control of steel structures represents a valid alternative to conventional seismic design methods. The seismic devices currently employed are mostly based on the metallic yielding technology due to the large feasibility and efficiency they can provide. Within this context, in the current paper an innovative solution based on the adoption of low-yield-strength pure aluminium shear panels (SPs) for seismic protection of steel moment-resisting frames is proposed and investigated. In order to prove the effectiveness of the system, a wide numerical study based on both static and dynamic non-linear analyses has been carried out, considering a number of different frame-to-shear panel combinations, aiming at assessing the effect of the main influential parameters on the seismic response of the structure. The obtained results show that the contribution provided by aluminium SPs is rather significant, allowing a remarkable improvement of the seismic performance of the structure in terms of stiffness, strength and ductility, with the possibility to strongly limit the damage occurring in the members of moment-resisting frames. In particular, it is clearly emphasized that the stiffening effect provided by SPs allows a more rational design procedure to be adopted, since the serviceability limit state check does not lead to unavoidable and uneconomical increase of the size of main structural members.